2005
DOI: 10.1016/j.ijforecast.2004.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Predicting real growth and the probability of recession in the Euro area using the yield spread

Abstract: IVIE working papers offer in advance the results of economic research under way in order to encourage a discussion process before sending them to scientific journals for their final publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 39 publications
3
33
1
1
Order By: Relevance
“…Rockinger [7]; Boldrin et al [8]; Estrella et al [9]; Vassalou [10]; Duarte et al [11]; Hong et al [12]; Clements and Galvao [13]; Cooper and Priestley [14]; Marcellino and Schumacher [15], amongst others). Theoretically, changes in industrial production lead to changes in activity, employment and liquidity in the economy.…”
Section: Open Accessmentioning
confidence: 99%
“…Rockinger [7]; Boldrin et al [8]; Estrella et al [9]; Vassalou [10]; Duarte et al [11]; Hong et al [12]; Clements and Galvao [13]; Cooper and Priestley [14]; Marcellino and Schumacher [15], amongst others). Theoretically, changes in industrial production lead to changes in activity, employment and liquidity in the economy.…”
Section: Open Accessmentioning
confidence: 99%
“…Preliminary analysis leads to the choice of lagged GDP growth as a threshold variable as found in Duarte et al (2005). The inclusion of the threshold is meant to improve the fit of the model and to monitor whether time varying behavior can in fact be traced back to threshold effects.…”
Section: State Dependent Threshold Models: Resultsmentioning
confidence: 99%
“…This relation was confirmed by Shaaf (2000), Ang, Piazzesi, and Wei (2006), Aretz and Peel (2008) and Bordo and Haubrich (2008), although Bordo and Haubrich reported that spreads only improved forecast in three of the nine sub-periods studied. Looking at this relation in a more international context, Esrella, Rogrigues and Schich (2003), Duarte, Venetis and Paya (2005) and Nakaoto (2005) found similar results in Germany, the Euro area and Japan, respectively. …”
mentioning
confidence: 79%